Provisioning, recovery, and in-operation planning in elastic optical network - Velasco, Luis, 1966-; Ruiz, Marc, 1981- (Hoboken, NJ : John Wiley & Sons, 2017)
Explains the importance of Elastic Optical Networks (EONs) and how they can be implemented by the world's carriers This book discusses Elastic Optical Networks (EONs) from an operational perspective. It presents algorithms that are suitable for real-time operation and includes experimental results to further demonstrate the feasibility of the approaches discussed. It covers practical issues such as provisioning, protection, and defragmentation. It also presents provisioning and recovery in single layer elastic optical networks (EON). The authors review algorithms for provisioning point-to-point, anycast, and multicast connections, as well as transfer-based connections for datacenter interconnection. They also include algorithms for recovery connections from failures in the optical layer and in-operation planning algorithms for EONs. Provisioning, Recovery and In-operation Planning in Elastic Optical Network also examines multi-layer scenarios. It covers virtual network topology reconfiguration and multi-layer recovery, and includes provisioning customer virtual networks and the use of data analytics in order to bring cognition to the network. In addition, the book: -Presents managing connections dynamically-and the flexibility to adapt the connection bitrate to the traffic needs fit well for new types of services, such as datacenter interconnection and Network Function Virtualization (NFV) -Examines the topic in a holistic and comprehensive way, addressing control and management plane issues for provisioning, recovery, and in-operation planning -Covers provisioning, recovery, and in-operation planning for EONs at the proposed exhaustive level The rapid expanse of new services has made the use of EONs (a relatively new concept) a necessity. That's why this book is perfect for students and researchers in the field of technologies for optical networks (specifically EONs), including network architectures and planning, dynamic connection provisioning, on-line network re-optimization, and control and management planes. It is also an important text for engineers and practitioners working for telecom network operators, service providers, and vendors that require knowledge on a rapidly evolving topic.
Motivation -- Background -- The routing and spectrum allocation problem -- Architectures for provisioning and in-operation planning -- Dynamic provisioning of P2P demands -- Transfer-based datacenter interconnection -- Provisioning multicast and anycast demands -- Spectrum defragmentation -- Restoration in the optical layer -- After failure repair optimization -- Virtual network topology design and reconfiguration -- Recovery in multilayer networks -- High capacity optical networks based on space division multiplexing -- Dynamic connectivity services in support of future mobile networks -- Towards cognitive in-operation planning.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on October 18, 2017).
Keywords: Optical engineering; Computer networks; Optics; TECHNOLOGY & ENGINEERING / Mechanical; Computer networks; Optical engineering; Optics; Electronic books